SISTEM BAGI HASIL USAHATANI JAGUNG PETANI PENGGARAP DI KECAMATAN PULUBALA KABUPATEN GORONTALO - Laila Umpul; Mahludin Baruwadi; Amelia Murtisari (Universitas Negeri Gorontalo, 2016)
This research aims at (1) Finding the system of revenue sharing of sharecropper corn farm in Sub-district of Pulubala, District of Gorontalo; (2) Finding the income of sharecropper corn farm in Sub-district of Pulubala, District of Gorontalo, by applying survey method. It is done in May-July 2016. It applies descriptive analysis and analysis of corn farm which are (), total of reception (TR), total of cost (TC). Findings show that (1) the system revenue sharing of corn farm in Sub-district of Pulubala is 3/4 of whole result. The system happens for presence of background factor between land owners with sharecropper derived from ancient time habit, kinship and agreement; (2) the average income of sharecropper corn farm in Sub-district of Pulubala, District of Gorontalo is IDR 5.820.640,25/season. Keywords: Revenue sharing, Corn farm, Sharecropper